Pragmatics and Prosody Illocution, Modality, Attitude, Information Patterning and Speech Annotation - Mello, Heliana; Panunzi, Alessandro; Raso, Tommaso (Strumenti per la didattica e la ricerca, 2012)
Most of the papers collected in this book resulted from presentations and discussions undertaken during the V Lablita Workshop that took place at the Federal University of Minas Gerais, Brazil, on August 23-25, 2011. The workshop was held in conjunction with the II Brazilian Seminar on Pragmatics and Prosody. The guiding themes for the joint event were illocution, modality, attitude, information patterning and speech annotation. Thus, all papers presented here are concerned with theoretical and methodological issues related to the study of speech. Among the papers in this volume, there are different theoretical orientations, which are mirrored through the methodological designs of studies pursued. However, all papers are based on the analysis of actual speech, be it from corpora or from experimental contexts trying to emulate natural speech. Prosody is the keyword that comes out from all the papers in this publication, which indicates the high standing of this category in relation to studies that are geared towards the understanding of major elements that are constitutive of the structuring of speech.